Composite coating metal plate with ultrahigh corrosion resistance and preparation method thereof
By applying a composite coating of zinc oxide nanosheets, non-fluorinated polymer resins and metal oxide particles on metal sheets, the lack of performance of the coating in the prior art under high temperature and high humidity environments is solved, efficient corrosion and wear resistance are achieved, and the service life of the metal material is extended.
Patent Information
- Application Number
- CN202510115396.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-24
- Publication Date
- 2025-04-25
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing metal anti-corrosion coating technology is difficult to provide sufficient protection in high temperature, high humidity and high corrosion environments, and the coating performance is degraded, resulting in corrosion or wear of metal materials, and it is difficult to achieve uniform distribution and effective combination of coating materials, resulting in unsatisfactory comprehensive performance.
A composite coating consisting of zinc oxide nanosheets, non-fluorinated polymer resin, molybdenum oxide and aluminum oxide particles is used to improve the corrosion resistance, wear resistance and construction performance of the coating by reasonably designing the components and their ratios, combined with the synergy of different materials.
It significantly improves the corrosion resistance and wear resistance of the coating, extends the service life of metal materials, and achieves the long-term durability and good construction performance of the coating in harsh environments.
Smart Images

Figure CN119875495A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of metal color-coated plates, and in particular to a composite coating metal plate with ultra-high corrosion resistance and a preparation method thereof. Background Art
[0002] Metal materials are widely used in various industrial fields. Metal sheets have become key basic materials in the construction, aviation, automobile and other industries due to their good mechanical properties and processing characteristics. However, metal surfaces are prone to corrosion when exposed to air, moisture, acidic and alkaline substances and other corrosive media, especially under harsh environmental conditions. Therefore, the anti-corrosion problem of metal materials has always been an important research direction in the fields of materials science and surface engineering.
[0003] Traditional metal anti-corrosion technologies mainly include coating technology, electroplating technology and thermal spraying technology. Coating technology is currently the most widely used anti-corrosion method. By coating a protective layer on the metal surface, the metal is isolated from the external environment, thereby avoiding metal corrosion. However, existing coating technology also has some limitations. For example, some coating materials are easily affected by factors such as ultraviolet rays, temperature, and mechanical friction, which leads to a decrease in coating performance, thereby affecting the long-term anti-corrosion effect of the metal. Especially for metal materials used in high temperature, high humidity, and high corrosion environments, existing coating technologies often cannot provide sufficient protection and are still prone to corrosion or wear.
[0004] In addition, traditional anti-corrosion coatings mostly use organic resin materials. Although these resins have good adhesion and processability, they are prone to aging in highly corrosive environments and have insufficient corrosion resistance. In order to solve this problem, in recent years, many studies have begun to focus on adding inorganic nanomaterials or metal oxide particles as reinforcing components to improve the corrosion resistance and wear resistance of the coating. These metal oxide materials have become a research hotspot for coating enhancers due to their excellent thermal and chemical stability.
[0005] However, although the addition of multiple reinforcing ingredients can improve the performance of the coating to a certain extent, there are still some unresolved problems in the existing technology. For example, how to achieve uniform distribution and effective combination of coating materials and avoid adverse interactions between different components has always been a difficulty in the research and development of coating materials. Existing metal coating materials often focus on one aspect in terms of performance, such as corrosion resistance or wear resistance, and it is difficult to achieve an effective balance and synergy between the two, resulting in unsatisfactory comprehensive performance of coating materials in practical applications.
[0006] Although the existing metal anti-corrosion coating technology has made some progress, it still faces several challenges in practical applications. First, the existing coating technology generally has the problem of insufficient corrosion resistance. Especially in extreme environments, the coating may fall off, age or crack, causing the metal to be exposed to corrosive media, thereby reducing the service life of the metal material. Secondly, wear resistance is also a major shortcoming of metal coating technology. In a mechanical friction environment, traditional coatings are easily worn, resulting in coating failure and exposing the metal substrate, which cannot play an effective anti-corrosion role.
[0007] Some studies have attempted to introduce inorganic nanomaterials, metal oxides or polymer composites into coatings in an attempt to improve the corrosion resistance and wear resistance of the coatings. However, although these methods have achieved certain results in unilateral performance improvement, it is often difficult to achieve the expected performance synergy due to compatibility issues between different components. For example, although some nanomaterials have excellent corrosion resistance, in high temperature and high humidity environments, the coating performance may be reduced due to poor interaction with the polymer matrix. In addition, the toughening and leveling properties of existing coatings are also insufficient, especially on thicker coatings or metal sheets with complex shapes. The coatings often cannot be applied evenly, resulting in unstable anti-corrosion effects.
[0008] These defects in the prior art indicate that simply relying on the addition of a certain type of material often cannot solve the multiple problems of metal anti-corrosion coatings in practical applications. Therefore, there is an urgent need for a composite coated metal sheet that can provide higher corrosion resistance, wear resistance and better construction performance, especially while ensuring the uniformity and stability of the coating, and can also achieve a synergistic effect of multiple properties to meet the needs of high-end application fields.
[0009] In the current technology, although the types and components of coating materials have been widely studied, it is still not possible to comprehensively improve the corrosion resistance, wear resistance and construction performance of metal coatings. To this end, the present invention aims to solve the shortcomings of the coating in the prior art in terms of corrosion resistance, wear resistance and uniform coating by rationally designing the components and ratios of the composite coating and combining the synergistic effect of different materials. Especially in high temperature, high humidity and high corrosion environments, the present invention needs to provide a composite coated metal sheet with ultra-high corrosion resistance, which can effectively deal with corrosion and wear problems under harsh conditions, thereby extending the service life of the metal material and meeting the performance requirements of the high-end industry for metal materials. Summary of the invention
[0010] In order to achieve the above-mentioned purpose of the invention and to solve the above-mentioned technical problems, the present invention provides a metal sheet with a composite coating having ultra-high corrosion resistance, wherein the metal sheet is composed of a metal plate and a composite coating supported on the metal plate, and the composite coating is prepared from the following components in parts by mass:
[0011] 8-15 parts of zinc oxide nanosheets, 12-18 parts of non-fluorinated polymer resin, 2-4 parts of toughening agent, 0.5-1 parts of leveling agent, 10-12 parts of solvent, 2-5 parts of metal oxide particles, and 0.5-2 parts of initiator.
[0012] Preferably, the metal plate is one of cold-rolled steel, stainless steel and aluminum alloy, and has a thickness ranging from 1 mm to 5 mm.
[0013] Preferably, the non-fluorinated polymer resin is polyamide-6 (PA-6) resin or polyphenylene sulfide (PPS) resin.
[0014] Preferably, the metal oxide particles are composed of molybdenum oxide (MoO3) and aluminum oxide (Al2O3) in a mass ratio of 1:1.5-1:2, and the particle size is less than 50 nm.
[0015] Preferably, the method for preparing the zinc oxide nanosheets comprises the following steps, with the components being calculated by weight:
[0016] 10 parts of 1-5 micron zinc oxide powder were mixed with 500 parts of deionized water, 100 parts of ammonia water were added and stirred evenly, and then reacted at 200°C and 15MPa for 4 hours. After the reaction was completed, the zinc oxide nanosheets were obtained by cooling and centrifugal separation to remove impurities, washing and drying.
[0017] Preferably, the toughening agent is one of polyurethane and chlorinated rubber, and the leveling agent is one of dimethyl silicone oil and polydimethylsiloxane.
[0018] Preferably, the initiator is benzoyl peroxide (BPO).
[0019] The present invention also provides a method for preparing the above-mentioned ultra-high corrosion resistance composite coating metal sheet, comprising the following steps:
[0020] S1 Preparation of zinc oxide nanosheets: 10 parts of 1-5 micron zinc oxide powder were mixed with 500 parts of deionized water, 100 parts of ammonia water were added and stirred evenly, and then reacted at 200°C and 15 MPa for 4 hours. After the reaction was completed, the mixture was cooled and centrifuged to remove impurities, and then washed and dried to obtain zinc oxide nanosheets;
[0021] S2 Preparation of non-fluorinated polymer resin coating: Mix the non-fluorinated polymer resin with the solvent, add the toughening agent and the leveling agent and stir until the resin solution is uniformly formed, then add the zinc oxide nanosheets to the resin solution and continue stirring to ensure that the zinc oxide nanosheets are evenly dispersed, then add the initiator benzoyl peroxide (BPO), the reaction temperature is 80°C, the reaction time is 4 hours, and the resin base material is obtained.
[0022] S3 Introduction of metal oxide particles: Add molybdenum oxide and aluminum oxide particles into the resin solution and disperse them evenly by an ultrasonic disperser;
[0023] S4 coating and curing: coating the coating solution on the metal plate, spraying and curing to obtain a composite coated metal sheet.
[0024] Preferably, the coating thickness of the composite coating is 50-70 μm.
[0025] Preferably, the composite coating is cured at 120° C. for 2-3 hours to form a dense and stable coating.
[0026] The technical solution provided by the present invention brings beneficial effects:
[0027] The addition of zinc oxide nanosheets in the present invention significantly enhances the corrosion resistance of the coating. Zinc oxide not only has good corrosion resistance, but also effectively enhances the bonding strength between polyamide-6 resin and metal substrate, forming a tighter structure and reducing the corrosion rate of the metal surface. Further introduction of molybdenum oxide (MoO3) and aluminum oxide (Al2O3) metal oxide particles further improves the stability and corrosion resistance of the coating through synergistic effects. The corrosion test results show that the corrosion rate of the coating in Example 1 is 1.48 mm·year -1 , which is significantly better than all the samples in the comparative examples, especially the sample in comparative example 3 without adding zinc oxide nanosheets, whose corrosion rate is as high as 90.15 mm·year -1 , verifying the key role of zinc oxide nanosheets and metal oxide particles in the anti-corrosion effect.
[0028] By rationally selecting a combination of zinc oxide nanosheets, non-fluorinated polymer resin, molybdenum oxide (MoO3) and aluminum oxide (Al2O3), the present invention avoids the limitations of traditional materials while maintaining a high anti-corrosion effect. In particular, the synergistic effect of molybdenum oxide and aluminum oxide further reduces the corrosion rate by improving the structural density and stability of the coating, and significantly prolongs the durability of the coating in harsh environments.
[0029] The present invention not only improves the anti-corrosion performance, but also takes into account the friction resistance of the coating. The experimental results show that the coating surface can maintain good sliding performance during the friction process. Compared with the coating using zinc oxide nanosheets in the comparative experiment, the embodiment also shows certain advantages in friction performance, especially when using different particles, the change in friction coefficient shows that the coating has good durability and stability.
[0030] In summary, the composite coating material of the present invention not only significantly improves the anti-corrosion performance of the material, but also optimizes its friction resistance through the synergistic effect of carefully selected components, especially zinc oxide nanosheets, non-fluorinated polymer resin and metal oxide particles. This technical solution can effectively solve the problems of poor anti-corrosion performance and insufficient friction resistance of coatings in the prior art, and has significant technical advantages and good application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 This is an optical microscope photograph of Example 1 of the present invention;
[0032] Figure 2 This is an optical microscope photograph of Comparative Example 1 of the present invention;
[0033] Figure 3 This is an optical microscope photograph of Comparative Example 2 of the present invention;
[0034] Figure 4 This is an optical microscope photograph of Comparative Example 3 of the present invention;
[0035] Figure 5 This is an optical microscope photograph of Comparative Example 4 of the present invention;
[0036] Figure 6 This is an optical microscope photograph of Comparative Example 5 of the present invention;
[0037] Figure 7 This is an optical microscope photograph of Comparative Example 6 of the present invention;
[0038] Figure 8 This is an optical microscope photograph of Comparative Example 7 of the present invention;
[0039] Fig. 9 This is a SEM photograph of Example 2 of the present invention. DETAILED DESCRIPTION
[0040] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. Of course, the specific embodiments described here are only used to explain the present invention and are not used to limit the present invention.
[0041] Example 1
[0042] Material preparation
[0043] Metal sheet: Choose cold rolled steel with a thickness of 3mm.
[0044] Zinc oxide nanosheets: Zinc oxide powder (particle size 1-5 microns) is used to prepare zinc oxide nanosheets, with a mass of 6 parts.
[0045] Non-fluorinated polymer resin: polyamide-6 (PA-6) resin is selected, with a mass of 16 parts.
[0046] Toughener: Choose polyurethane, 3 parts by mass.
[0047] Leveling agent: Use polydimethylsiloxane with a mass of 0.8 parts.
[0048] Solvent: Dimethyl sulfoxide (DMSO) was selected, with a mass of 11 parts.
[0049] Metal oxide particles: Molybdenum oxide (MoO3) and aluminum oxide (Al2O3) are selected, the mass ratio of the two is 1:1.8, the particle size is less than 50nm, and the mass is 3 parts.
[0050] Initiator: Use benzoyl peroxide (BPO), the mass is 1 part.
[0051] Preparation process
[0052] S1. Preparation of zinc oxide nanosheets:
[0053] Mix 10 parts of zinc oxide powder with 500 parts of deionized water, add 100 parts of ammonia water, and stir evenly;
[0054] The reaction was carried out at 200°C and 15 MPa for 4 hours, and then cooled after the reaction was completed;
[0055] Impurities are removed by centrifugal separation, and zinc oxide nanosheets are obtained by washing and drying.
[0056] S2. Preparation of non-fluorinated polymer resin coating:
[0057] Mix polyamide-6 (PA-6) resin with 16 parts of solvent (DMSO), add 3 parts of polyurethane toughening agent and 0.8 parts of leveling agent, and stir until the resin solution is uniformly formed;
[0058] Add 12 parts of zinc oxide nanosheets obtained in step 1 to the resin solution and continue stirring to ensure that the zinc oxide nanosheets are evenly dispersed;
[0059] 1 part of benzoyl peroxide (BPO) was added, and the reaction temperature was set to 80° C. and the reaction time was 4 hours to obtain a resin base material.
[0060] S3. Introduction of metal oxide particles:
[0061] Add 4 parts of molybdenum oxide (MoO3) and aluminum oxide (Al2O3) particles into the resin solution and disperse them evenly using an ultrasonic disperser to ensure that the metal oxide particles are fully mixed with the resin solution.
[0062] S4. Coating and curing:
[0063] The prepared coating solution is evenly applied on the surface of the cold-rolled steel metal plate by spraying;
[0064] The coated metal plate was cured at 120° C. for 2.5 hours to form a dense and stable composite coating; the coating thickness was controlled at about 55 μm.
[0065] Example 2
[0066] The preparation method was the same as that in Example 1, except that the mass of the zinc oxide nanosheets was 15 parts
[0067] Example 3
[0068] The method is the same as that of Example 1, except that the non-fluorinated polymer resin is polyphenylene sulfide (PPS) resin.
[0069] Example 4
[0070] The preparation was carried out in the same manner as in Example 1, except that the mass ratio of molybdenum oxide (MoO3) to aluminum oxide (Al2O3) was 1:1.5.
[0071] Example 5
[0072] The preparation was carried out in the same manner as in Example 1, except that the mass ratio of molybdenum oxide (MoO3) to aluminum oxide (Al2O3) was 1:2.
[0073] Comparative Example 1
[0074] The preparation was carried out in the same manner as in Example 1, except that nano zinc oxide with a particle size of 100 nm was used instead of zinc oxide nanosheets.
[0075] Comparative Example 2
[0076] The preparation was carried out in the same manner as in Example 1, except that nano-titanium dioxide with a particle size of 100 nm was used instead of zinc oxide nanosheets.
[0077] Comparative Example 3
[0078] The preparation was carried out in the same manner as in Example 1, except that no zinc oxide nanosheets were added.
[0079] Comparative Example 4
[0080] The preparation was carried out in the same manner as in Example 1, except that no metal oxide particles were added.
[0081] Comparative Example 5
[0082] The preparation was carried out in the same manner as in Example 1, except that all the metal oxide particles were replaced by aluminum oxide (Al2O3).
[0083] Comparative Example 6
[0084] The same preparation method as in Example 1 was used for preparation, except that manganese oxide (MnO2) was used instead of molybdenum oxide (MoO3), and calcium oxide (CaO) was used instead of aluminum oxide (Al2O3).
[0085] Comparative Example 7
[0086] The preparation was carried out in the same manner as in Example 1, except that all the metal oxide particles were replaced by zinc oxide nanosheets.
[0087] Experimental test:
[0088] 1. Corrosion test:
[0089] Ingredients: Copper sulfate solution 10%, 30mL; Calcium chloride solution 10%, 30mL; Magnesium chloride solution 5%, 20mL
[0090] Ammonium chloride solution 5%, 10mL; hydrochloric acid solution 0.1mol / L, 1mL
[0091] Experimental steps: Dissolve copper sulfate, calcium chloride, magnesium chloride, and ammonium chloride in water to prepare a solution with the above proportions. Add 1 mL of hydrochloric acid and mix well. Use a dropper to drop the mixture on the coating surface and record the time when corrosion occurs. Observe whether corrosion occurs on the coating surface and record the time when corrosion begins to evaluate the corrosion resistance of the coating.
[0092] 2. Optical microscope (optical scanning image)
[0093] Light source setting: adjusted to 30°-45°; Light source type: ring light source;
[0094] Contrast: 70%-80%, Brightness: 50%-60%;
[0095] Polarizer: circularly polarized light source;
[0096] Image contrast adjustment: 70%-90%,
[0097] 3. Electrochemical corrosion
[0098] The three-electrode structure is adopted, with the coating material as the working electrode, graphite as the counter electrode, and silver chloride electrode (SCE) as the reference electrode. The area of the working electrode is 1cm 2, 3.5wt% NaCl solution was used as the electrolyte solution. Before measurement, the working electrode was immersed in the electrolyte for 20 minutes to establish a stable open circuit potential (OCP). The Tafel polarization curve was collected at a scan rate of 1mv / s. -2 Hz-10 -3 Electrochemical impedance spectroscopy was performed on the AC signal in the frequency range of Hz.
[0099] Icorr (μA·cm-2): corrosion current density; Ecorr (mV): corrosion potential; Corrosion Rate (mm·year-1): corrosion rate.
[0100] 4. Friction resistance test
[0101] The wear resistance test is carried out in accordance with ISO 7784-2. A 60g weight wrapped in non-woven fabric is loaded on the coating sample. It is then moved horizontally on the coating surface 1000 times. The wear resistance is evaluated by monitoring the water contact angle of the coating sample and the changes before and after friction.
[0102] 5. Conventional performance test
[0103] Standard: "HGT3830-2022 Pre-coated coil coatings",
[0104] Table 1 Electrochemical corrosion data
[0105]
[0106]
[0107] The composite coating material of the present invention significantly improves the anti-corrosion performance through precise component design, especially the synergy between zinc oxide nanosheets, non-fluorinated polymer resin and metal oxide particles. In Example 1, the combination of zinc oxide nanosheets and polyamide-6 resin, with metal oxide particles of molybdenum oxide (MoO3) and aluminum oxide (Al2O3), effectively enhances the structural stability and corrosion resistance of the coating, which is significantly superior to all materials in the comparative examples.
[0108] Especially in the application of zinc oxide nanosheets, zinc oxide not only provides good corrosion resistance, but also plays a role in enhancing the bonding between the polymer matrix and the metal surface in the coating. At the same time, the synergistic effect of molybdenum oxide and aluminum oxide further reduces the corrosion rate by enhancing the structural density and stability of the coating, ensuring the long-term protection effect of the coating in harsh environments.
[0109] Comparative experiments show that if nano zinc oxide (Comparative Example 1) or nano titanium dioxide (Comparative Example 2) is used, the corrosion performance is greatly reduced and the corrosion rate is significantly increased (22.98 mm·year -1 and 20.12mm·year -1 ), proving the decisive influence of particle size and material type on the anti-corrosion performance. In addition, without adding zinc oxide nanosheets (Comparative Example 3) or metal oxide particles (Comparative Example 4), the anti-corrosion effect of the coating deteriorated sharply, with a corrosion rate of 90.15 mm·year -1 , which is significantly lower than Example 1. These results further verify the synergistic effect of the components in the present invention, that is, the combination of different materials can produce a complementary effect on the anti-corrosion performance, which is significantly better than using any component alone.
[0110] In summary, the composite coating of the present invention significantly improves the corrosion resistance of the material by rationally selecting and combining different functional components, especially the synergistic effect between zinc oxide nanosheets, non-fluorinated polymer resin and metal oxide particles, exhibits excellent technical effects, and ensures the long-term durability of the coating in harsh environments.
[0111] Table 2 Friction resistance test data
[0112] Material Contact angle front (°) Water contact angle (°) Friction coefficient before After friction coefficient Example 1 91.2 87.6 0.15 0.18 Example 2 92.3 88.5 0.16 0.20 Example 3 89.7 84.2 0.18 0.21 Example 4 85.4 81.9 0.20 0.24 Example 5 87.9 83.3 0.17 0.19 Comparative Example 1 78.5 74.0 0.22 0.26 Comparative Example 2 75.3 71.2 0.23 0.28 Comparative Example 3 65.4 62.1 0.30 0.35 Comparative Example 4 72.6 69.7 0.25 0.29 Comparative Example 5 77.8 73.5 0.21 0.25 Comparative Example 6 88.4 83.2 0.17 0.20 Comparative Example 7 79.0 75.5 0.19 0.22
[0113] The composite coating in the embodiment of the present invention shows obvious advantages in friction resistance. The application of zinc oxide nanosheets helps to reduce the friction coefficient, and the synergistic effect of the metal oxide particles further optimizes the performance of the coating. In particular, in Example 5, the best friction resistance is achieved by optimizing the ratio of metal oxides.
[0114] Through comparative experiments, it can be clearly seen that compared with the examples, the comparative solutions using zinc oxide with larger particle size or different materials all show higher friction coefficients. In particular, comparative example 3 (without adding zinc oxide nanosheets) and comparative example 4 (without adding metal oxide particles) perform the worst, significantly lower than the examples. This shows that zinc oxide nanosheets and metal oxide particles are key factors in improving friction resistance.
[0115] Therefore, the composite coating material of the present invention significantly improves the friction resistance of the coating by rationally designing the composition and structure, especially the synergistic effect of zinc oxide nanosheets and metal oxide particles, verifying the beneficial effects of the invention.
[0116] Table 3 Conventional performance test data
[0117]
[0118] The test results show that all samples show stable and good performance in terms of hardness, chemical resistance and water boiling performance. The hardness of the coating is in the higher range, the chemical resistance is excellent, and the water boiling performance is stable. Some samples show slight softening in water boiling performance, but it does not cause serious loss of physical properties. These results show that the designed coating material has good physical and chemical stability and is suitable for a variety of application scenarios.
[0119] From the results of corrosion tests and optical microscope image analysis, Example 1 of the present invention exhibits significant corrosion resistance and excellent surface structure. The composite coating of zinc oxide nanosheets and metal oxide particles exhibits the best effect in corrosion resistance and mechanical strength. The optical microscope photos further confirm this point. The surface structure of the coating in Example 1 is dense and uniform, with no obvious cracks or particle aggregation, which enhances the performance of the coating. In contrast, the various comparative examples in the experiment ( Figures 2 to 8 ), the lack or replacement of key components (such as zinc oxide nanosheets and metal oxide particles) leads to poor dispersion of the coating, significant cracks and unevenness, which in turn affects the mechanical strength and corrosion resistance of the coating. Overall, the coating technology of the present invention provides an efficient solution, significantly improves the corrosion resistance and mechanical stability of metal sheets, and has high practical value and innovation.
[0120] Figure 8 Scanning electron microscope (SEM) images show the flaky structure of zinc oxide nanosheets, which are mostly stacked together and overlapped with each other, presenting a multi-layer superposition state. They appear as well-dispersed flakes, which are conducive to dispersion in the coating solution to form a comprehensive isolation barrier.
[0121] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A metal sheet with a composite coating having ultra-high corrosion resistance, characterized in that: The metal sheet is composed of a metal plate and a composite coating supported on the metal plate, and the composite coating is prepared from the following components in parts by mass: 8-15 parts of zinc oxide nanosheets, 12-18 parts of non-fluorinated polymer resin, 2-4 parts of toughening agent, 0.5-1 parts of leveling agent, 10-12 parts of solvent, 2-5 parts of metal oxide particles, and 0.5-2 parts of initiator.
2. The ultra-high corrosion resistance composite coating metal sheet according to claim 1, characterized in that: The metal plate is one of cold-rolled steel, stainless steel and aluminum alloy, and has a thickness ranging from 1 mm to 5 mm.
3. The ultra-high corrosion resistance composite coating metal sheet according to claim 1, characterized in that: The non-fluorinated polymer resin is polyamide-6 (PA-6) resin or polyphenylene sulfide (PPS) resin.
4. The ultra-high corrosion resistance composite coating metal sheet according to claim 1, characterized in that: The metal oxide particles are composed of molybdenum oxide (MoO3) and aluminum oxide (Al2O3) with a mass ratio of 1:1.5-1:2 and a particle size of less than 50nm.
5. The ultra-high corrosion resistance composite coating metal sheet according to claim 1, characterized in that: The preparation method of the zinc oxide nanosheets comprises the following steps, with the components being calculated by weight: 10 parts of 1-5 micron zinc oxide powder were mixed with 500 parts of deionized water, 100 parts of ammonia water were added and stirred evenly, and then reacted at 200°C and 15MPa for 4 hours. After the reaction was completed, the zinc oxide nanosheets were obtained by cooling and centrifugal separation to remove impurities, washing and drying.
6. The ultra-high corrosion resistance composite coating metal sheet according to claim 1, characterized in that: The toughening agent is one of polyurethane and chlorinated rubber, and the leveling agent is one of dimethyl silicone oil and polydimethylsiloxane.
7. The ultra-high corrosion resistance composite coating metal sheet according to claim 1, characterized in that: The initiator is benzoyl peroxide (BPO).
8. A method for preparing a metal sheet with a composite coating having ultra-high corrosion resistance according to any one of claims 1 to 6, comprising the following steps: S1 Preparation of zinc oxide nanosheets: 10 parts of 1-5 micron zinc oxide powder were mixed with 500 parts of deionized water, 100 parts of ammonia water were added and stirred evenly, and then reacted at 200°C and 15 MPa for 4 hours. After the reaction was completed, the mixture was cooled and centrifuged to remove impurities, and then washed and dried to obtain zinc oxide nanosheets; S2 Preparation of non-fluorinated polymer resin coating: Mix the non-fluorinated polymer resin with the solvent, add the toughening agent and the leveling agent and stir until the resin solution is uniformly formed, then add the zinc oxide nanosheets to the resin solution, and continue stirring to ensure that the zinc oxide nanosheets are uniformly dispersed, then add the initiator benzoyl peroxide (BPO), the reaction temperature is 80°C, the reaction time is 4 hours, and the resin base material is obtained; S3 Introduction of metal oxide particles: Molybdenum oxide and aluminum oxide particles are added to the resin solution and dispersed evenly by an ultrasonic disperser; S4 coating and curing: coating the coating solution on the metal plate, spraying and curing to obtain a composite coated metal sheet.
9. The method for preparing the ultra-high corrosion resistance composite coating metal sheet according to claim 8, characterized in that: The coating thickness of the composite coating is 50-70 μm.
10. The method for preparing the ultra-high anti-corrosion composite coating metal sheet according to claim 7, characterized in that: The composite coating was cured at 120° C. for 2-3 hours.
Citation Information
Patent Citations
Fluorine-free polyphenylene sulfide super-hydrophobic coating and preparation method thereof
CN109337573A
A waterborne polyamide prepolymer slurry and its preparation method
CN114933850A